Factors associated with prescription opioid overdose deaths in patients with non-cancer pain: a literature review - Ismail, Fadhilah; Zin, Che Suraya (2015)
Opioid analgesics have increasingly been prescribed in the treatment of non -cancer pain and this trend has accompanied increasing rates of opioid overdose deaths (ODs). Little is known about the factors that may predispose an individual to being at risk for fatal overdose from prescription opioids. This review examined factors associated with prescription opioid overdose deaths in patients with non-cancer pain. A comprehensive literature search was conducted for studies published from 2004 to 2014 using databases such as Science Direct, PubMed, Web of Science, Cochrane review and Scopus. Articles were included if they were original research studies written in English that reported deaths with prescription opioid overdose in patients with non-cancer pain. A total of 18 studies met the inclusion criteria and were included. Fndings from the review demonstrated that concomitant use of opioids with benzodiazepines (polysubstance use) was the main factor associated with opioid ODs. Codeine and oxycodone were more commonly reported to cause opioid ODs and opioid doses of more than 100 mg per day in morphine equivalents have higher risk to cause ODs. Other factors included male patients, middle aged and having mental illness. Prescription opioid overdose deaths were primarily caused by concomitant use of opioid with benzodiazepines. Further research is required to examine the trend and patterns of this co-prescribing. The guidelines on opioid prescribing and education on opioids for both patients and physicians should be emphasized to reduce fatalities from overdose while enhancing the safe prescribing of opioids.